Analisis Fungsi Produksi dan Efisiensi Penggunaan Input pada Usahatani Jagung di Kecamatan Kabawo Kabupaten Muna - Wa Ode Ifana; Usman Rianse; Weka Gusmiarty Abdullah; R. Marsuki Iswandi; Budiyanto Budiyanto; Ine Fausayana (Universitas Halu Oleo, 2021)
This study aims to determine the factors that influence the production of corn farming, and to determine the efficiency of corn farming. The population in this study were all corn farmers in Kabawo District, Muna Regency. The sample in this study amounted to 85 farmers. Sampling was carried out using a stratified random sampling technique. The analytical method used is multiple nonlinear regression with the Cobb-Douglas production function model, data envelopment analysis (DEA) and marginal value product. The results showed that the factors that had a significant effect on the production of corn farming were seed production, land area, seeds, herbicides, labor and farming skills. Production factors that have no significant effect on corn farming are fertilizers, insecticides, number of dependents, farming experience and access to information. Analysis of technical efficiency through the production function Data Envelopment Analysis (DEA), shows that the average production value achieved by technical efficiency is 0.855 or 88.5%. In terms of price efficiency through the calculation of price efficiency analysis, the input use of land area and seeds is not efficient, while the input use of fertilizers, insecticides, herbicides and labor is not efficient. Economically, the use of land inputs, seeds, fertilizers, herbicides, insecticides and labor is not efficient.Keywords: corn farming; Cobb-Douglas; production factors; efficiency